Social & behavioral risk factors and early childhood caries – a cross-sectional study on preschool children in Shah Alam / Norashikin Yusof, Luqman Arif Muhammad Ghazali and Nur Shahirah Zulkifle - Yusof, Norashikin; Muhammad Ghazali, Luqman Arif; Zulkifle, Nur Shahirah (Faculty of Dentistry, Universiti Teknologi MARA, 2021)
Early childhood caries (ECC) remains a major challenge among the 5-6 year olds in Malaysia with a caries prevalence of 71.3% as indicated in the last survey of preschool children in 2015. Studies have shown that behavior and income status can influence development of ECC. The aim of this study was to measure the caries prevalence among 2 – 5 years old preschool children and to study the association of parents’ socio behavioral factors on ECC. 140 preschool children participated in this study. Parents were given a set of structured questionnaires and oral examination was conducted on their children after receiving consent. Findings showed prevalence of dental caries was 50.1% with mean dft score of 2.51. There was significant association between dental caries and children drinking formula milk and sweet drinks in their bottles: (p<0.05). Children from lower income family and lower education level have significantly higher caries prevalence compared to those from more privileged family. Drinking pattern, family income and education level appear to be contributing factors towards development of ECC among this group of children. It is recommended that health promotion interventions be targeted towards the lower income group with emphasis on drinking pattern of the children.